2018
DOI: 10.1126/science.aau5174
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of widespread type I and type V CRISPR-Cas inhibitors

Abstract: Bacterial CRISPR-Cas systems protect their host from bacteriophages and other mobile genetic elements. Mobile elements, in turn, encode various anti-CRISPR (Acr) proteins to inhibit the immune function of CRISPR-Cas. To date, Acr proteins have been discovered for type I (subtypes I-D, I-E, and I-F) and type II (II-A and II-C) but not other CRISPR systems. Here, we report the discovery of 12 genes, including inhibitors of type V-A and I-C CRISPR systems. AcrVA1 inhibits a broad spectrum of Cas12a (Cpf1) ortholo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
251
1
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 239 publications
(284 citation statements)
references
References 27 publications
9
251
1
2
Order By: Relevance
“…However, creating 'designer' inhibitors for specific gene editors and editing scenarios is very challenging as Acr proteins are small and lack any sequence and structural conservation to use for direct identification of desired modalities. To overcome these problems, approaches such as screening 13 self-targeting genomes (7,10,19) or metagenomic DNA (13,14) attempt to cast a wide net in the genomic space to identify novel Acr activities. A more direct method is to use a 'guilt-byassociation' search approach, which leverages the repeated observations that Acrs tend to coexist in similar operons and that the genomic neighborhood of several Acrs contain anti-CRISPR associated (aca) genes that are closely coupled with Acrs, and widespread in bacteria and MGEs.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, creating 'designer' inhibitors for specific gene editors and editing scenarios is very challenging as Acr proteins are small and lack any sequence and structural conservation to use for direct identification of desired modalities. To overcome these problems, approaches such as screening 13 self-targeting genomes (7,10,19) or metagenomic DNA (13,14) attempt to cast a wide net in the genomic space to identify novel Acr activities. A more direct method is to use a 'guilt-byassociation' search approach, which leverages the repeated observations that Acrs tend to coexist in similar operons and that the genomic neighborhood of several Acrs contain anti-CRISPR associated (aca) genes that are closely coupled with Acrs, and widespread in bacteria and MGEs.…”
Section: Discussionmentioning
confidence: 99%
“…However, some MGEs, particularly phages, have evolved anti-CRISPRs (Acrs), peptide inhibitors of Cas proteins that block CRISPR defense systems (2,3). Acrs have been discovered to inhibit distinct CRISPR systems, including type I (4)(5)(6)(7)(8), type II (9)(10)(11)(12)(13)(14)(15)(16), type III (17,18), and type V (7,19). Strategies for identifying new Acrs include testing genes of unknown function that are proximal to anti-CRISPR associated (aca) genes (5-7, 9, 15) and screening genes in organisms with self-targeting CRISPR systems (7,19,20).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, Watters et al [20] identified three targeted Acrs (AcrVA1, AcrVA4, and AcrVA5) from M. bovoculi that inhibit or attenuate CRISPR-Cas12a (type V)-based genome editing in human cells. Marino et al [22] also concurrently reported the discovery of AcrVA1, AcrVA2, and AcrVA3 from M. bovoculi and confirmed that AcrVA1 inhibits a broad spectrum of Cas12a orthologs, including M. bovoculi Cas12a (MbCas12a), Acidaminococcus sp. Cas12a (AsCas12a), and Lachnospiraceae bacterium Cas12a (LbCas12a), when assayed in mammalian cells.…”
Section: Type V Anti-crispr Proteinsmentioning
confidence: 79%
“…The first reported case of CRISPR protein inhibition in 2013 targeted the type I-F system from Pseudomonas aeruginosa (P. aeruginosa) [12], and the following year, four anti-CRISPR proteins (Acrs) targeting the type I-E systems were identified [13]. Subsequently, many types of type I Acr proteins have been systematically discovered, and because Acr research has proceeded quickly, recent studies have successively identified many Acr types that inhibit type I (I-E, I-F, I-D, I-C), type II (II-A, II-C), type III (III-B), and type V (Cas12a, also known as Cpf1) proteins [16][17][18][19][20][21][22][23][24]. Although the mechanism and function of Acrs have been systematically summarized by several recent reviews [25][26][27][28][29], their deeper and wider application as a potential tool for regulating CRISPR-Cas systems for gene editing deserves further attention from researchers.…”
Section: Introductionmentioning
confidence: 99%